Deformation of Earth’s upper mantle: insights from naturally occurring fabric types - Gray, Erin M. (Curtin University, 2013)
Flow of the Earth’s upper mantle is controlled by the rheology of olivine, therefore comprehending the factors affecting olivine fabric development is critical for understanding global tectonic processes. Microstructural, FTIR and isotope analysis of olivine in Higashi-akaishi and Lihir peridotites provides insight into the relationship between olivine deformation, geochemistry and water. These results have fundamental implications for interpreting seismic anisotropy and are applicable to a wide range of tectonic environments to better constrain mantle deformation.